locum tua tempora poscunt: topography in Ovid’s Fasti - Heyworth, SJ (Cambridge University Press, 2024)
For narrative and theme, space like time is a key element in the Fasti of Ovid as well as the Metamorphoses. After an initial exploration of the programmatic establishment of the theme of place in each poem, this chapter focuses on the thematic use of geography in the Fasti. The first section reflects on the prominence given to Rome’s physical and metaphorical place in the world: it is the city to which migrants travel, from which armies depart, to which victorious generals return with new sacra. The poem also treats Rome as urban space, and uses topography to help give meaning to sequences of adjacent temples and festivals. The final section touches on how Ovid’s own exile gives depth to the presentation both of Rome and of travel in the wider world: things are out of place.